FRI0271 The SPARCC/SPARTAN (SPAR) reference imaging module for calibration of readers scoring with the msasss: Preliminary validation. (23rd January 2014) - Maksymowych, W.; Learch, T.; Lambert, R.; Ward, M.; Haroon, N.; Salonen, D.; Inman, R.; Weisman, M.
Abstract : Background: The modified Stoke Ankylosing Spondylitis Spine Score (mSASSS) is increasingly used to assess disease severity and progression in patients with AS but the methodology is still not well standardized. The Spondyloarthritis Research Consortium of Canada (SPARCC) and the SPondyloArthritis Research and Treatment Network (SPARTAN) have formed a working group to develop and validate a reference image module aimed at calibration of readers using the mSASSS. Objectives: To develop and validate a reference imaging module aimed at standardization of the approach to scoring radiographic damage using the mSASSS. Methods: The working group comprises 5 rheumatologists with variable experience in using the mSASSS and 3 musculoskeletal radiologists with special expertise in AS. The following sequence of developmental steps preceded the first scoring exercise: 1. Systematic review of the literature pertaining to radiographic scoring in AS to identify aspects of the mSASSS requiring methodological clarity. 2. Independent assessment blinded to time point of baseline and 2 year radiographs from 25 patients with AS using the mSASSS (pilot exercise). 3. Group meeting aimed at debriefing of discrepant scores, identification of gaps or lack of clarity in methodology, consensus development of uniform rules for scoring. 4. Development of an imaging module (the SPAR module) through consensus which clarifies definitions, rules and scoring methodology, and a set of reference radiographic images. A formal scoring exercise was then conducted by 6 readers on 39 patients with AS, which included 15 from the pilot exercise, where baseline and 2 year radiographs were scored blinded to time point. Reliability of the mSASSS was assessed by the intraclass correlation method (ICC). Results: This process led to the development of the SPAR module comprised of 70 slides which describe the following: 1. Consensus definitions for squaring, erosions, sclerosis, 2. Consensus rules for scoring syndesmophytes (degenerative versus spondylitic, growth remote from vertebral corners) and ankylosis (including ossification in the disc space and remote from vertebral corners), 3. The approach to missing observations. The group has concluded that only syndesmophytes and ankylosis should be scored in the cervical spine, and that the antero-posterior lumbar spine radiograph be assessed together with the lateral radiograph in scoring the lumbar spine. The pilot exercise demonstrated excellent reliability for status scores (ICC for 6 readers (range) =0.92; Median (range) ICC for 15 reader pairs =0.92 (0.84-0.96)) but poor reliability for change scores (ICC for 6 readers =0.46; Median (range) for 15 reader pairs =0.52 (0.11-0.66)). In particular, ICC for change score for the radiologist reading pair was only 0.46. In the formal scoring exercise, the ICC for change score for the radiologist reading pair improved substantially to 0.62 although overall reliability for change score for the entire group improved marginally (ICC for 6 readers =0.49). Conclusions: Reliable assessment of change in mSASSS is very challenging though can be improved for expert readers if they are calibrated according to the standardized methodology in the SPAR module. Disclosure of Interest: None Declared